AN ANDROID-BASED APPLICATION TO IMPROVE THE ABILITY TO DRAW AND INTERPRET FBD - Kurniawan, Yohanes; Jelatu, Silfanus; Adi, Nugroho Prasetya; Kurnila, Valeria Suryani (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
The aim of this study is to develop an Android-based learning application which is named worked example mechanics. This application was made for learning classical mechanics class IX Natural Sciences Program in Indonesia. This application is specifically designed to train and improve students' ability to draw and interprete Free Body Diagram (FBD). This application contains classic mechanic material content, animated learning of classical mechanics, drawing exercises and interpreting FBD  and a self-evaluation system. This application has passed the feasibility test of both the material and the media by Yogyakarta Negeri University physics learning experts. The app is also useful in enhancing the ability to interpret FBD, in trials at Sekolah Menengah Atas 2 Kupang/SMAN 2 Kupang (State Senior High School 2 Kupang), SMAN 3 Kupang, SMA TIMPOLMAS Kupang and State Alyah Madrasah (MAN) 1 Yogyakarta